Correlation between Parenting Skills, Children’s Emotional and Intelligence Quotient with School Readiness - Mashar, Riana; Pudji Astuti, Febru (JPUD - Jurnal Pendidikan Usia Dini, 2022)
School readiness is critical to academic achievement in first grade. However, often parents only focus on cognitive readiness without paying much attention to children’s emotional factors and parental factors that affect school readiness. This study aims to identify the relationship between parenting skills, emotional quotient (EQ), intelligence (IQ), and children’s school readiness. This study uses a correlation design that focuses on parental and internal factors. The research subjects were parents and students from 21 kindergartens in Magelang (n=165) who were selected through simple random sampling. Data collection was carried out through online questionnaires for parents, Raven Intelligence Scale, EQ Scale, and school readiness tests for children. The data obtained were analyzed through regression analysis techniques. The results of the study show that emotional intelligence has the strongest correlation with school readiness. Intelligence also correlates with children’s school readiness. However, there is no significant correlation between parental skills and children’s school readiness. Based on gender, there is no significant difference in school readiness between boys and girls. The findings of this study imply that school readiness needs to be improved by developing children’s emotional intelligence as important as cognitive intelligence. Keywords: parenting skills, children’s EQ and IQ, school readiness References: Arnold, C., Bartlett, K., Gowani, S., & Shallwani, S. (2008). Transition to school: Reflections on readiness. Journal of Developmental Processes, 3(2), 26–38. Blankson, A. N., Miner, J., Leerkes, E. M., O’Brien, M., Calkins, S. D., & Marcovitch, S. (2017). Cognitive and Emotional Processes as Predictors of a Successful Transition into School HHS Public Access. Early Educ Dev, 28(1), 1–20. https://doi.org/10.1080/10409289.2016.1183434 Cohen, J. (2006). Social, emotional, ethical, and academic education: Creating a climate for learning, participation in democracy and well-being. Harvard Educational Review, 76(2), 201–237. Coolahan, Kathleen, Mendez, Julia, Fantuzzo, John; McDermott, P. (2020). Preschool peer interactions and readiness to learn: Relationships between classroom peer play and learning behaviors and conduct. Journal of Educational Psychology, 92(3), 458–465. https://doi.org/10.1016/j.dr.2019.01.001.The Creswell, J. W. (2015). Educational research: Planning, conducting, and evaluating quantitative and qualitative research (Fifth edition). Pearson. Crnic, Keith Lamberty, G. (1994). Reconsidering school readiness: Conceptual and applied perspectives. Early Education and Development, 5(2), 91–105. Dawson, Courtney; Huitt, W. G. (2011). Running head: Social Development. April. Edwards, C. P., Sheridan, S. M., & Lisa, K. (2008). Digital Commons @ University of Nebraska—Lincoln Parent Engagement and School Readiness: Parent- Child Relationships in Early Learning. Faculty Publications, Department of Child, Youth, and Family Studies, 60(September). Janus, M., & Offord, D. A. N. (1997). To Learn at School. 71–75. Janus, M., & Offord, D. R. (2007). Development and psychometric properties of the Early Development Instrument (EDI): A measure of children’s school readiness. Canadian Journal of Behavioural Science, 39(1), 1–22. https://doi.org/10.1037/cjbs2007001 Lucy S. King, 1 Kathryn L. Humphreys, 2 and Ian H. Gotlib1. (2020). The Neglect–Enrichment Continuum: Characterizing Variation in Early Caregiving Environments. HHS Public Asses. Lunenburg, F. C. (2011). Early Childhood Education: Implications for School Readiness. 2(1), 1–8. McLanahan, S., Haskins, R., Paxson, C., Rouse, C., & Sawhill, I. (2005). The Future of Children: School Readiness: Closing Racial and Ethnic Gaps Affairs. In The Future of Children (Vol. 15, Issue 1). Oyserman, D., Brickman, D., & Rhodes, M. (2007). School success, possible selves, and parent school involvement. Family Relations, 56(5). https://doi.org/10.1111/j.1741-3729.2007.00475.x Pagani, L. S., & Fitzpatrick, C. (2014). Children’s School Readiness: Implications for Eliminating Future Disparities in Health and Education. Health Education and Behavior, 41(1), 25–33. https://doi.org/10.1177/1090198113478818 Pagani, L. S., & Messier, S. (2012). Links between Motor Skills and Indicators of School Readiness at Kindergarten Entry in Urban Disadvantaged Children. Journal of Educational and Developmental Psychology, 2(1), 95–107. https://doi.org/10.5539/jedp.v2n1p95 Pianta, R. C., Barnett, W. S., Burchinal, M., & Thornburg, K. R. (2009). The effects of preschool education: What we know, how public policy is or is not aligned with the evidence base, and what we need to know. Psychological Science in the Public Interest, Supplement, 10(2), 49–88. https://doi.org/10.1177/1529100610381908 Raver, C., & Knitze, J. (2002). Ready to Enter: What Research Tells Policymakers About Strategies to Promote Social and Emotional School Readiness Among Three- and Four-Year-Old Children. Promoting the Emotional Well-Being of Children and Families, 3, 1–24. Sari, Y. D. L. A. (2019). Analysis of parental involvement in learning assistance in early childhood. [Analisis keterlibatan orang tua dalam pendampingan pembelajaran pada anak usia dini]. Jurnal Caksana-Pendidikan Anak Usia Dini, 2(1), 22–38. Shaari, M. F., & Ahmad, S. S. (2016). Physical Learning Environment: Impact on Children School Readiness in Malaysian Preschools. Procedia - Social and Behavioral Sciences, 222, 9–18. https://doi.org/10.1016/j.sbspro.2016.05.164 Shan, W., Zhang, Y., Zhao, J., Zhang, Y., Cheung, E. F. C., Chan, R. C. K., & Jiang, F. (2019). Association between Maltreatment, Positive Parent–Child Interaction, and Psychosocial Well-Being in Young Children. Journal of Paediatrics, 213. https://doi.org/10.1016/j.jpeds.2019.06.050 Shonkoff, J. P., & Phillips, D. A. (Eds.). (2000). From neurons to neighbourhoods: The science of early childhood development. National Academy Press. Sudarsih, W. (2011). Social Skills [Keterampilan Sosial]. Repository.Upi. Edu, 12–35. Utami, N. R., & Novitasari, K. (2020). Developing a Multirepresentation Learning Model Based on Local Wisdom to Transform Character for Students Of 5-6 Years Old. Early Childhood Education and Development Journal, 1(2), 9. https://doi.org/10.20961/ecedj.v1i2.35362 Xiao Zhang; Bi Ying Hu; Lixin Ren; Meifang. (2019). Young Chinese Children’s Academic Skill Development: Identifying Child-, Family-, and School-Level Factors: Young Chinese Children’s Academic Skill Development. New Directions for Child and Adolescent Development 2019(3), 3. Xing, X., & Wang, M. (2018). The moderating role of HPA activity in the relations between parental corporal punishment and executive function in Chinese school-aged children. Psychology of Violence, 8(4), 418–426., 8(4), 418-426.